Characterizing wind power resource reliability in southern Africa - Charles Fant; Udaya Bhaskar Gunturu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Producing electricity from wind is attractive because it provides a clean, low-maintenance power supply. However, wind resource is intermittent on various time scales, thus introducing variability in power output that is difficult for electric grid planning. In the following study, wind resource is characterized using metrics that highlight these intermittency issues, therefore identifying areas of high and low wind power reliability in southern Africa at different time scales. After developing a wind speed profile, these metrics are applied at various heights in order to assess the added benefit of raising the wind turbine hub. Furthermore, since the interconnection of wind farms can aid in reducing the overall intermittency, the value of interconnecting near-by sites is mapped using three distinct methods. Of the countries in this region, the Republic of South Africa has shown the most interest in wind power investment. For this reason, we focus parts of the study on wind resource in the country. The study finds that, although wind power density is high in South Africa compared to its neighboring countries, wind power resource tends to be less reliable than in other parts of southern Africa - namely, central Tanzania and parts of Kenya. We also find that South Africa's potential varies over different time scales, with higher potential in the summer than winter, and higher potential during the day than at night. This study is concluded by introducing a variety of methods and measures to characterize the value of interconnection, including the use of principal component analysis to single out areas with a common signal.
Keywords: Q41; Q42; Q54; 330; wind power; intermittency; reliability; renewable energy; Africa; South Africa